IMAGE QUALITY ASSESSMENT GUIDED COLLABARATIVE LEARNING OF IMAGE ENHANCEMENT AND CLASSIFICATION OF DR GRADING - Mrs.K.SONI, M. NIHARIKA, R. SAI DURGA, K. MAMATHA (Pegem Journal of Education and Instruction, 2023)
Diabetic Retinopathy (DR) is a significant cause of blindness worldwide, and its early detection is essential for timely treatment and prevention of severe vision loss. Accurate grading of DR is critical for appropriate clinical decision-making, which requires both image enhancement and classification.This paper proposes a novel approach for DR grading by leveraging Image Quality Assessment (IQA) guided collaborative learning of image enhancement and classification.